Montezuma's Daughter - Haggard, H. Rider (Henry Rider), 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2006)
"Montezuma's Daughter" by H. Rider Haggard is a novel published in 1893. Englishman Thomas Wingfield embarks on a quest for vengeance after his mother's murder, leading him through the Spanish Inquisition, shipwreck, and slavery. Unwillingly joining a Spanish expedition to New Spain, he witnesses the brutal clash between European conquistadors and native civilizations. Amidst war and misunderstanding, Thomas marries Otomie, daughter of an Aztec emperor, finding love in a world torn apart by conquest and cultural collision. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Montezuma%27s_Daughter
Release date is 2006-05-14
Donald Lainson, Anonymous Volunteers and David Widger
Keywords: Mexico -- History -- Conquest, 1519-1540 -- Fiction